Pengaruh Kepemimpinan, Dukungan Sosial, dan Stres Kerja terhadap Kepuasan Kerja pada Perawat di Rumah Sakit Umum Syifa Medika Banjarbaru - Hanifah Hanifah; Erini Junita Sari; Muhammad Fauzan (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to examine the influence of leadership, social support, and job stress on job satisfaction among nurses at Syifa Medika General Hospital, Banjarbaru. This study is a qualitative study. Primary data were collected from questionnaire responses. Total sampling was used as the sampling technique. Descriptive analysis was used as the analysis method. The data analysis results indicate that leadership influences job satisfaction, while social support and job stress do not.